Imperial power and places of worship in the numismatic representations of Claudius - Mancini, Willian (Romanitas - Revista de Estudos Grecolatinos, 2015)
The numismatic sources are an important vestige to understand aspects of ancient societies. One of these aspects that are elucidated by this type of source is the religious one, represented through praised deities, important temples or rituals. In the context of the Roman Empire, one realizes that this theme shares space with the imperial power and the purpose of establishing a local identity. The objective of this article is to show through numismatic emissions as this process occurred in some localities of the Principate of Claudius.
Keywords: Claudius; Roman Empire; Numismatic; Religious aspects; Local identity